Organizational Behavior Third Edition (Organizational behavior: emerging realities for the workplace revolution) - Steven Lattimore McSane (McGraw-Hill, 2005)
Program dan File dalam bentuk Gambar, Rtf, Htm (internet), dll; Isi: McShane (Build your management skill, Chapter Summaries, Flashcards, Obonline, dll), Support, Extras, dll; Judul dalam kemasan.